Bimekizumab in patients with active psoriatic arthritis: results from a 48-week, randomised, double-blind, placebo-controlled, dose-ranging phase 2b trial. Issue 10222 (8th February 2020) - Ritchlin, Christopher T; Kavanaugh, Arthur; Merola, Joseph F; Schett, Georg; Scher, Jose U; Warren, Richard B; Gottlieb, Alice B; Assudani, Deepak; Bedford-Rice, Kathy; Coarse, Jason; Ink, Barbara; McInnes, Iain B
Summary: Background: Dual neutralisation of interleukin 17A (IL17A) and interleukin 17F (IL17F) is a potential novel therapeutic approach in psoriatic arthritis. We assessed bimekizumab, a monoclonal antibody that selectively neutralises IL17A and IL17F, in patients with active psoriatic arthritis. Methods: BE ACTIVE was a randomised, double-blind, placebo-controlled, dose-ranging phase 2b study done at 41 sites in the Czech Republic, Germany, Hungary, Poland, Russia, and the USA. Eligible patients aged 18 years or older with active adult-onset psoriatic arthritis and symptoms for at least 6 months were randomly assigned (1:1:1:1:1) to placebo, 16 mg bimekizumab, 160 mg bimekizumab, 160 mg bimekizumab with a one-off 320 mg loading dose, or 320 mg bimekizumab, which were administered as subcutaneous injections every 4 weeks for 12 weeks. After 12 weeks, patients assigned to the placebo and 16 mg bimekizumab groups were randomly reassigned (1:1) to either 160 mg or 320 mg bimekizumab, and all other patients remained on their originally assigned initial dose up to 48 weeks. Both participants and researchers were blinded to treatment allocation in the first 12 weeks, and blinded to the dose of bimekizumab thereafter. The primary endpoint was the proportion of patients with at least 50% improvement in the American College of Rheumatology response criteria at week 12, which was assessed in all patients who received at least one dose of study treatment and had a valid measurement of the primary efficacy endpoint at baseline. The trial, including all follow-up, has been completed. This trial is registered with ClinicalTrials.gov, NCT02969525 . Findings: Between Oct 27, 2016, and July 16, 2018, 308 patients were screened, and 206 were randomly assigned: 42 to the placebo group, and 41 each to the four bimekizumab groups. At 12 weeks, compared with the placebo group, significantly more patients in the 16 mg bimekizumab (odds ratio [OR] 4·2 [95% CI 1·1–15·2]; p=0·032), 160 mg bimekizumab (8·1 [2·3–28·7]; p=0·0012), and 160 mg (loading dose) bimekizumab (9·7 [2·7–34·3]; p=0·0004) groups achieved an ACR50 response. At 12 weeks, 24 (57%) of 42 patients in the placebo group and 68 (41%) of the 164 patients in the bimekizumab groups reported treatment-emergent adverse events. Most of these adverse events were mild or moderate. Serious treatment-emergent adverse events occurred in nine patients, eight of whom were receiving bimekizumab. No deaths or cases of inflammatory bowel disease were reported. Interpretation: Bimekizumab doses of 16 mg and 160 mg (with or without a 320 mg loading dose) were associated with significant improvements in ACR50 compared with placebo, with an acceptable safety profile. Our results support phase 3 investigation of bimekizumab as a treatment for psoriatic arthritis. Funding: UCB Pharma.